Generalized polyspike train: An EEG biomarker of drug-resistant idiopathic generalized epilepsy. (6th November 2018) - Sun, Yanping; Seneviratne, Udaya; Perucca, Piero; Chen, Zhibin; Tan, Meng Kee; O'Brien, Terence J.; D'Souza, Wendyl; Kwan, Patrick
Abstract : Objective: To identify clinical and EEG biomarkers of drug resistance in adults with idiopathic generalized epilepsy. Methods: We conducted a case-control study consisting of a discovery cohort and a replication cohort independently assessed at 2 different centers. In each center, patients with the idiopathic generalized epilepsy phenotype and generalized spike-wave discharges on EEG were classified as drug-resistant or drug-responsive. EEG changes were classified into predefined patterns and compared between the 2 groups in the discovery cohort. Factors associated with drug resistance in multivariable analysis were tested in the replication cohort. Results: The discovery cohort included 85 patients (29% drug-resistant and 71% drug-responsive). Their median age at assessment was 32 years and 50.6% were female. Multivariable analysis showed that higher number of seizure types ever experienced (3 vs 1: odds ratio [OR] = 31.1, 95% confidence interval [CI]: 4.5–214, p < 0.001; 3 vs 2: OR = 14.6, 95% CI: 2.3–93.1, p = 0.004) and generalized polyspike train (burst of generalized rhythmic spikes lasting less than 1 second) during sleep were associated with drug resistance (OR = 10.8, 95% CI: 2.4–49.4, p = 0.002). When these factors were tested in the replication cohort of 80 patients (27.5% drug-resistant and 72.5% drug-responsive; 71.3% female; median age 27.5 years), the proportion of patients with generalized polyspike train during sleep was also higher in the drug-resistant group (OR = 4.0, 95% CI: 1.35–11.8, p = 0.012). Conclusion: Generalized polyspike train during sleep may be an EEG biomarker for drug resistance in adults with idiopathic generalized epilepsy.